KETELADANAN HIDUP MENURUT 1 TIMOTIUS 4:12 DAN IMPLEMENTASINYA KEPADA REMAJA DI JEMAAT GMIM SION MALALAYANG - Sege, Anastasya Tesalonika; Selanno, Semuel; Thomas, Art Semuel (ATOHEMA: Jurnal Teologi Pastoral Konseling, 2024)
The purpose of this study is to realize the nature and responsibility and concern in understanding the existence of adolescents to instill good spiritual values for teenagers so that teenagers can also be an example for people without making age a measure. The research was conducted on teenagers in the GMIM Sion Malalayang congregation to find out how teenagers understand the exemplary life according to 1 Timothy 4: 12. The approach used in this research is to use a qualitative approach as well as by conducting interviews and observations. Based on the results of the research that has been done, it can be said that teenagers do not understand the exemplary life according to 1 Timothy 4:12 so that the principles of exemplary life in it cannot be applied properly by teenagers. therefore teenagers should understand as well as possible the context and application of exemplary life from 1 Timothy 4:12 and of course there needs to be support from the surrounding environment such as church and parents / adults